A standard formulation for the installation of suction caissons in sand - Ayed Eid Alluqmani; Muhammad Tayyab Naqash; Ouahid Harireche (Journal of Ocean Engineering and Science, 2019)
Suction assisted installation of caisson foundations in sand relies on the developed seepage around the caisson wall. Seepage is known to produce soil loosening inside the caisson cavity and an overall reduction in soil resistance to caisson penetration. On the other hand, suction must be controlled so that no excessive piping is induced within the sand volume trapped inside the caisson cavity. When it extends over the full embedded length of the caisson wall, piping may lead to the formation of piping channels, which may compromise the established seal between caisson and soil and ultimately cause the installation process to stop. A safe installation process requires a proper design procedure to ensure that a safe suction can be predicted prior to installation. The present paper provides a framework where analytical expressions are obtained for the required suction magnitude, and for the critical suction that causes piping to initiate at the caisson tip. These analytical expressions are derived for a normalized caisson geometry, based on compiled results obtained from finite element analysis of seepage around a caisson wall, at various installation depths. The developed analytical formulation applies independently of caisson dimensions such as diameter, height and wall thickness. Critical suction for piping condition is also obtained under analytical form as a function of normalized penetration depth. The developed formulation can also be easily incorporated into design procedures or used in design codes without a need for a preliminary seepage analysis to be undertaken. The proposed suction predictions for the whole process of caisson installation in sand are validated against field trials reported in the literature. Keywords: Suction caisson, Normalized seepage problem, Polynomial regressions, Suction profile, Critical suction for piping